Early daratumumab therapy improves renal outcomes in newly diagnosed patients with myeloma admitted with kidney injury - E. Bridget Kim; Jack E. Malespini; Matthew Lei; Samuel S. Han; Cole W. Minsky; Andrew R. Branagan; Elizabeth K. O’Donnell; Diana Cirstea; Noopur S. Raje; Andrew J. Yee (Blood Advances, 2025)
Abstract: Cast nephropathy is the most common cause of acute kidney injury (AKI) in patients with multiple myeloma (MM). A prompt reversal of renal injury is paramount for improving clinical outcomes. Daratumumab, an anti-CD38 monoclonal antibody, has significant clinical efficacy in MM. We describe the effects of daratumumab-based therapy in 20 patients admitted with a new diagnosis of MM and AKI with a median creatinine of 6.5 mg/dL. All patients (100%) achieved serum free light chain (sFLC) reduction ≥50% within the first cycle, with a median time to sFLC reduction ≥50% of 3 days (95% confidence interval [CI], 3-7). Of 17 patients, 15 (88%) achieved sFLC reduction ≤500 mg/L after 1 cycle of treatment. The median time to sFLC reduction ≤500 mg/L was 14.5 days (95% CI, 9-49). The overall renal response at 3 months was 85% (n = 17), with complete, partial, and minor responses in 50% (n = 10), 10% (n = 2), and 25% (n = 5), respectively. Of the 9 patients who required dialysis at presentation, 4 of 7 (57.1%) and 6 of 7 (85.7%) were dialysis independent at 3 and 12 months, respectively. Hematologic overall response rate was 100%, with very good partial response (VGPR) in 90%. With a median follow-up of 25 months, progression-free survival was 46.5 months (95% CI, 11.9 to not reached), and the 2-year overall survival was 83.7% (95% CI, 68.4-100). These findings highlight the importance of early initiation of daratumumab-based treatment in patients with MM and AKI to induce rapid and significant reductions in sFLCs, improve renal outcomes, and provide an approach without plasmapheresis.